The sociological imagination - Mills, C. Wright (Charles Wright), 1916-1962 (Tantor Media, Inc., 2021)
C. Wright Mills is best remembered for his highly acclaimed work The Sociological Imagination, in which he set forth his views on how social science should be pursued. Hailed upon publication as a cogent and hard-hitting critique, The Sociological Imagination took issue with the ascendant schools of sociology in the United States, calling for a humanist sociology connecting the social, personal, and historical dimensions of our lives. The sociological imagination Mills calls for is a sociological vision, a way of looking at the world that can see links between the apparently private problems of the individual and important social issues.